-6(x+1)=6-5x

Simple and best practice solution for -6(x+1)=6-5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(x+1)=6-5x equation:


Simplifying
-6(x + 1) = 6 + -5x

Reorder the terms:
-6(1 + x) = 6 + -5x
(1 * -6 + x * -6) = 6 + -5x
(-6 + -6x) = 6 + -5x

Solving
-6 + -6x = 6 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
-6 + -6x + 5x = 6 + -5x + 5x

Combine like terms: -6x + 5x = -1x
-6 + -1x = 6 + -5x + 5x

Combine like terms: -5x + 5x = 0
-6 + -1x = 6 + 0
-6 + -1x = 6

Add '6' to each side of the equation.
-6 + 6 + -1x = 6 + 6

Combine like terms: -6 + 6 = 0
0 + -1x = 6 + 6
-1x = 6 + 6

Combine like terms: 6 + 6 = 12
-1x = 12

Divide each side by '-1'.
x = -12

Simplifying
x = -12

See similar equations:

| 36+36-18= | | ln(1-3x)+C=ln(x)+C | | 81x^2+18x+6=equation | | 7x+1=9x+(-17) | | 10-16x-6-5x=7 | | -15=-4m+5[5] | | .16(y-3)+.04=.14y-.03(30) | | x+(x*.20)+(x*.10)=5000 | | 12x+1=11x+3 | | 23-p=8 | | 6+5(-7+7v)=146 | | w^2+8w-9=0 | | x+(x-6)=116 | | 10+6=-2(7x-8) | | 85=5(1+4n) | | 12x+9-4x-4=7-x+30 | | 4x+37-6x=3-8x+4 | | 4(3x+7)=-17+21 | | 2(6n+1)=62 | | -8+3x-4=5x+10 | | 12x+4=11x+11 | | 6(3-z)*5=-z | | 9=4p+6-p | | 3x+3=8x+13 | | 200x-1400= | | 4(-3+1)=-8 | | 6q=30q | | y^5-2y^3+y=0 | | 6(3-2x)=42 | | 4(7r+3)=236 | | x+7+x+7-17=17 | | x+7+x+7-17=11 |

Equations solver categories